ANALISIS KUANTITAS, KUALITAS DAN TINGKAT KEMATANGAN BATUAN INDUK FORMASI KLASAFET MENGGUNAKAN TOTAL ORGANIC CARBON (TOC) DAN ROCK-EVAL PYROLYSIS (REP) STUDI KASUS SUMUR KYANITE-1 - Hastowo Resesiyanto (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2021)
The Salawati Basin is one of the basins located in the western part of the Bird's Head of Papua Island and is estimated to be of Tertiary. This basin was formed as a result of the activity of the Sorong Fault which began to be active since the Early Pleistocene. One of the rock formations that has the potential to become source rock in the Salawati Basin is the Klasafet Formation. The age of Klasafet Formation is between Middle Miocene and Late Miocene, which consists of claystone and limestone. Geochemical analysis is one of the techniques in interpreting the source rock potential. This analysis consists of three parts, namely the analysis of quantity, quality and maturity level of the source rock. From the results of the quantity analysis of source rock for the Klasafet Formation, the Total Organic Carbon (TOC) value ranges from fair to good. The quality analysis shows that the source rock of the Klasafet Formation tends to produce type III kerogen, while the maturity level analysis of the Klasafet Formation is in the immature-early mature zone.